Okoliczności dopuszczające rozpoznanie sprawy o nieważność małżeństwa w procesie skróconym przed biskupem - Nowicka, Urszula (Ius Matrimoniale, 2015)
Article 14 § 1 Ratio procedendi ((the official explanation which accompanied the new norms Mitis Iudex Dominus Iesus) sets forth the various types of cases which qualify to be instructed according to the briefer process before the Bishop according to cann. 1683-1687. Among the circumstances includes for example: the defect of faith which can generate simulation of consent or error that determines the will; a brief conjugal cohabitation; an abortion procured to avoid procreation; an obstinate persistence in an extraconjugal relationship at the time of the wedding or immediately following it; the deceitful concealment of sterility, or grave contagious illness, or children from a previous relationship, or incarcerations; a cause of marriage completely extraneous to married life, or consisting of the unexpected pregnancy of the woman, physical violence inflicted to extort consent, the defect of the use of reason which is proved by medical documents, etc. The circumstances are analyzed in this article.